OPTIMIZATION OF THE HYDRODYNAMICS OF GATING-FEEDING SYSTEMS IN ACCORDANCE WITH THE USE OF NEURO NETWORKS METHODS OF CLASSIFICATION OF TECHNOLOGICAL PARAMETERS - I. B. Odarchenko; V. A. Zharanau; I. N. Prusenko (Литьë и металлургия, 2018)
The method of optimizing the design of gating-feeding systems on the basis of the automated classification algorithm of technological complexity of the casting is presented.